1998
DOI: 10.1159/000017093
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Sulfate Decreases the Interleukin-2-Mediated Overactivity of the Natural Killer Cell Compartment in Senile Dementia of the Alzheimer Type

Abstract: Since dehydroepiandrosterone sulfate (DHEAS) has been involved in the regulation of cellular immunity, the aim of the presence study was to evaluate whether the age-dependent reduction of DHEAS was associated with changes of natural killer (NK) immune function in healthy elderly subjects and in patients with senile dementia of the Alzheimer type (SDAT). Circulating DHEAS was determined throughout 24 h (circadian profile). NK cytotoxic activity was measured as spontaneous and induced cytotoxicity during exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Coincidentally, cortical oxygenation increases slightly and MAP increases progressively. These effects are probably blood‐pressure independent because (1) our data (Figure 4E and 4F) show that the direct relation between MAP and pO 2 is depressed in the cortex and lost in the medulla after chronic NOS inhibition, and (2) previous findings show that renal alterations induced by NO deficiency cannot be restored by antihypertensive treatment 57. Welch et al showed that low renal oxygenation and inefficient oxygen consumption were not subject to hypertension in the spontaneously hypertensive rat 58…”
Section: Discussionmentioning
confidence: 60%
“…Coincidentally, cortical oxygenation increases slightly and MAP increases progressively. These effects are probably blood‐pressure independent because (1) our data (Figure 4E and 4F) show that the direct relation between MAP and pO 2 is depressed in the cortex and lost in the medulla after chronic NOS inhibition, and (2) previous findings show that renal alterations induced by NO deficiency cannot be restored by antihypertensive treatment 57. Welch et al showed that low renal oxygenation and inefficient oxygen consumption were not subject to hypertension in the spontaneously hypertensive rat 58…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, DHEA would seem a more desirable choice for therapeutic intervention if it possessed effective antiinflammatory activity against Alzheimer-relevant stimuli. Promising effects of DHEA-S on hypersensitive natural killer cells in Alzheimer have been reported (Solerte et al, 1999). A role for lymphocytes in Alzheimer disease has not been established, however.…”
Section: Discussionmentioning
confidence: 99%
“…AT 1 receptor blockade normalized blood pressure in both strains, suggesting that the AT 1 receptor mediates the impaired renal sodium excretion and blood pressure elevation induced by NO synthesis blockade. However, in experiments conducted in rats treated for 8 weeks with a NOS inhibitor, renin-angiotensin system blockade normalized blood pressure but had no effect on the pressure-natriuresis responses, implying that correction of NOS inhibitor-induced HTN is not enough to overcome the renal alterations associated with the chronic deficiency of NO [61]. These findings highlight the complex interactions between Ang II and NO and indicate that they play an important pathogenetic role in the development of HTN.…”
Section: Salt Sensitivity and Female Sex Hormonesmentioning
confidence: 99%